Chargеs collection efficiency in gamma-ray detectors with different electrodes configuration - Kondrik, A. I. (Technology and design in electronic equipment, 2012)
The dependence of the charge collection efficiency n in gamma-ray detectors based on CdZnTe on the impurity composition of the material has been investigated. Plane-parallel, cylindrical and spherical electrodes have been considered. A comparative analysis of n for detectors with electrodes of different shape has been carried out and the optimum composition of the material CdxZn1–xTe placed in the electrode gap has been determined.